The cross and the curtain. Mies or the modern iconoclasm - Espuelas, Fernando (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The ideological position that rejects the symbolic use of human images has been recurrent throughout history. Propaganda in the service of power, whether political or religious, has made an overwhelming use of image. However, from time to time, due to exhaustion or weariness, contrary reactions occur that lead to the prohibition of the symbolic use of the image of the human body. At the beginning of the 20th century, the visual resources of the avant-garde relapsed into this inclination to dispense with the human image and replace it with artifacts or pure abstraction. In accordance with an idealism not far from the Platonic, the abstraction of the Modern Movement intensifies in the void that reflects the architecture of Mies. This position leads to consider the disturbing human presence of that perfect order, and, consequently, to dispense with it, in what can be understood as a form of modern iconoclasm. The cross and the curtain are metonyms of the mechanisms to eliminate and replace the image and the human presence itself.